Influence on emergency digit replantation and outcome assessment after COVID-19 virus nucleic acid testing normalization - Zhang, Kunqi; Zhang, Rui; Li, Shanyu; Liu, Shenghe; Wang, Feiyan; Xu, Jia; Kang, Qinglin (Frontiers in Surgery, 2023)
Objective The study aims to compare the implementation and prognosis of emergency digit replantation surgery before and after normalized corona virus disease 2019 (COVID-19) nucleic acid testing for patients taking emergency operation and to explore the influence of normalized COVID-19 nucleic acid testing on replantation surgery. Method Normalized COVID-19 nucleic acid testing for patients taking emergency operation has been carried out since 1 August 2021 at our hospital, which means each patient who needs emergency surgical treatment has to obtain either positive or negative results of COVID-19 nucleic acid before entering the operating room. This research reviewed and compared the prognosis of the injured extremity that had emergency severed digit replantation between June and September 2021, at the Shanghai Sixth People's Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, and analyzed the impact of normalized COVID-19 nucleic acid testing on the outcome of the replanted fingers of different severity using disability of arm-shoulder-hand (DASH) and hand injury severity scoring (HISS) scoring systems. Results A total of 54 cases with 74 severed replanted phalanges were included replanted by the research group between 1 August and 30 September 2021, without any COVID-19 suspected/confirmed case detected. Compared with previous period (1 June to 31 July, 2021), although the interval between emergency visits and emergency replantation did increase significantly after normalized COVID-19 nucleic acid testing [(3.83 ± 0.94) to (1.77 ± 0.67) h, P < 0.05], we observed no significant difference in the improvement rate of the DASH scoring of the disabled upper extremity 3-month postoperatively (P = 0.538) nor in the complication rate (P = 0.344). Moreover, there was no significant difference in the improvement rate of the DASH scoring of the disabled upper extremity 3-month postoperatively in patients with different traumatic severities before and after normalized COVID-19 nucleic acid testing (moderate P = 0.269, severe P = 0.055, major P = 0.149). Conclusion Despite the preoperative delay, the policy of COVID-19 nucleic acid testing normalization does not have explicit influence on the short-term outcomes of emergency digit replantation surgery. With this evidence, microsurgeons could pay attention to the patients' anxiety and spend more effort in comforting them during the prolonged preoperative wait. These insights may have implications for other emergency department resource management whenever a social crisis occurs.